297. Risk Factors for Infections in Open Fractures. (26th November 2018) - Reisfeld, Sharon; Labnawi, Islam; Shadmi, Nurit; Stein, Michal
Abstract: Background: Open fractures are more prone to get infected. Known risk factors are high grade Gustilo and patients' co-morbidities, while early antibiotic administration and surgical debridement decrease the risk of infection. There is little data regarding the preferred antimicrobial therapy, timing, and duration of treatment, especially in the era of antimicrobial resistance. The aim of our study was to compare patients with and without infections after open fractures, and identify risk factors for infections, including timing of antimicrobial first dose and its duration. Methods: A historical cohort study was conducted in a secondary hospital. All adult patients admitted to the hospital with an open fracture of the limbs, between January 1, 2012 and December 31, 2016 were included in the study. Epidemiological, clinical, and microbiological data were collected and analyzed. Microbiological infection was defined by positive wound cultures during first 30 days, and clinical infection as defined by the treating physician. Results: One hundred sixty-seven patients were included in the study. One hundred sixty patients (95%) were treated with a first generation cephalosporine, and 55 (33%) were also treated with aminoglycosides. Microbiological infection was identified in 12 (7%) patients, and clinical infection in 27 (16%) patients. All patients received the first dose of antimicrobial therapy within 15 hours of admission (median 1.29 hours). Early administration of the first dose of antimicrobial therapy did not reduce the risk of infection (median of 1.06 hours for patients who developed infection vs. 1.31 hours for patients that did not develop infection, P = 0.58). Duration of treatment was not correlated to the risk of infection (1–3 days vs. 4–7 days, P = 0.6). In multivariate logistic regression, only location of fracture in the lower limbs was associated with an increased risk of infection (OR 4.654, CI 1.407–15.398), and Gustilo grade 1 or 2 were associated with decreased risk of infection (OR 0.301, CI 0.104–0.872). Conclusion: In our cohort, neither early administration of antimicrobial therapy, nor prolonged duration of treatment, reduced the risk of infection in open fractures. Disclosures: All authors: No reported disclosures.